The Use of Speech Level in Socio Cultural Perspetive of Tapal Kuda Madurese Ethnic Society - Haryono, Akhmad; Wibisono, Bambang (PAROLE: Journal of Linguistics and Education, 2018)
Madurese society at Tapal Kuda regions has a unique cultural tradition because of cultural acculturation with other ethnics. This research aims at describing the speech level use in socio cultural perspective of Madurese ethnic society in Tapal Kuda regions. The method used to reach the research aims is a qualitative method with an ethnographic approach. The data were collected through participatory and non-participatory observations, interviews, note-taking, and recording. The data collected were transcribed into the written data and then analysed with pragmatic theory. The use of BM with E-E, Ng-E, and È-B variation in the perspective of Madurese ethnic in Tapal Kuda is as the politeness implementation form and formal relationship among speech participants, whereas variation of BM E-I (ngoko: Javanese) in family is used to keep intimacy and closed relationship between parents and children in order not to be too formal.